Heart failure and mortality outcomes in patients with type 2 diabetes taking alogliptin versus placebo in EXAMINE: a multicentre, randomised, double-blind trial. Issue 9982 (23rd May 2015) - Zannad, Faiez; Cannon, Christopher P; Cushman, William C; Bakris, George L; Menon, Venu; Perez, Alfonso T; Fleck, Penny R; Mehta, Cyrus R; Kupfer, Stuart; Wilson, Craig; Lam, Hung; White, William B; et al.
Summary: Background: The EXAMINE trial showed non-inferiority of the DPP-4 inhibitor alogliptin to placebo on major adverse cardiac event (MACE) rates in patients with type 2 diabetes and recent acute coronary syndromes. Concerns about excessive rates of in-hospital heart failure in another DPP-4 inhibitor trial have been reported. We therefore assessed hospital admission for heart failure in the EXAMINE trial. Methods: Patients with type 2 diabetes and an acute coronary syndrome event in the previous 15–90 days were randomly assigned alogliptin or placebo plus standard treatment for diabetes and cardiovascular disease prevention. The prespecified exploratory extended MACE endpoint was all-cause mortality, non-fatal myocardial infarction, non-fatal stroke, urgent revascularisation due to unstable angina, and hospital admission for heart failure. The post-hoc analyses were of cardiovascular death and hospital admission for heart failure, assessed by history of heart failure and brain natriuretic peptide (BNP) concentration at baseline. We also assessed changes in N-terminal pro-BNP (NT-pro-BNP) from baseline to 6 months. This study is registered with ClinicalTrials.gov, number NCT00968708 . Findings: 5380 patients were assigned to alogliptin (n=2701) or placebo (n=2679) and followed up for a median of 533 days (IQR 280–751). The exploratory extended MACE endpoint was seen in 433 (16·0%) patients assigned to alogliptin and in 441 (16·5%) assigned to placebo (hazard ratio [HR] 0·98, 95% CI 0·86–1·12). Hospital admission for heart failure was the first event in 85 (3·1%) patients taking alogliptin compared with 79 (2·9%) taking placebo (HR 1·07, 95% CI 0·79–1·46). Alogliptin had no effect on composite events of cardiovascular death and hospital admission for heart failure in the post hoc analysis (HR 1·00, 95% CI 0·82–1·21) and results did not differ by baseline BNP concentration. NT-pro-BNP concentrations decreased significantly and similarly in the two groups. Interpretation: In patients with type 2 diabetes and recent acute coronary syndromes, alogliptin did not increase the risk of heart failure outcomes. Funding: Takeda Development Center Americas.